Insecticides resistance of brown planthopper (Nilaparvata lugens) from integrated agriculture development area (IADA) utara, Kerian, Perak Darul Ridzuan - Khairuddin, Muhammad Afandi (2014)
Brown planthopper (Nilaparvatalugens) is a serious pest in rice field because it causes a directdamage to rice plant and also as a vector several serious viruses. Intensive use of similar insecticide at rice field in Malaysia has result a low mortality of BPH population today. Therefore, a study of insecticide resistance to BPH and what type of level is of great interest because if resistance could be monitored, the population and the disease that came from BPH can easily be controlled. Applying the insecticide to BPH not only can cause of resistance but also could bring another impact such as the mortality of natural enemies, BPH resurgence, effect on human health and polluting the environment. In this case studies, BPH will be collected at rice field at Kerian, Perak by using an aspirator and transfer into mylar cages in glasshouse. Taichung Native 1 of variety rice will be the planted as a food for BPH in insect rearing process where until the instar of BPH will develop into female adult. Two types of insecticide will be used in this study (Imidacloprid and Fipronil) to determine resistant level. Insecticides treatment will be applied topically on the thoracic region of insects. Mortality observation was recorded after 24 hours and 48 hours. The results from bioassays demonstrated that BPH population in 2013 has developed resistance to Imidacloprid and less resistance towards Fipronil with resistance ratio ranging from 2.71-fold and 0.59-fold respectively. By comparing BPH population in 2013 with results from 2012, Fipronil has the highest toxicity level as having the lowest LD50values (1.05 – 67.26 μg/g) which mean it needed only small amount of insecticides to kill half of the population. Meanwhile, Imidacloprid have least toxicity at range (1.05 – 67.26 μg/g) respectively.